The Influence of Compensation, Career Development, and Job Satisfaction on Employee Retention - Silvia Hendrayanti; Laksmi Larassati (Universitas Negeri Semarang, 2024)
The development of a company cannot be separated from the support of all parties inside and outside the company. One of them comes from Human Resources (HR) which is closely related to employees. This study aims to analyze the implementation of company support in influencing employee retention of PT Oranje Nutrisi Global Semarang. The population in this study was all employees of PT Oranje Nutrisi Global Semarang. The sample was determined by saturated sampling technique according to the population of 31 respondents because the population was relatively small. This study also used multiple linear regression tests using the IBM SPSS Statistic 23 program. The findings of this study explain that: (1) Compensation has a significant positive effect on employee retention of PT Oranje Nutrisi Global Semarang because of the significance value of 0.023 < 0.05. (2) Career development has a significant positive effect on employee retention of PT Oranje Nutrisi Global Semarang because it has a significance value of 0.041 < 0.05. (3) Job Satisfaction has a significant positive effect on employee retention of PT Oranje Nutrisi Global Semarang because of the significance value of 0.043 < 0.05. Suggestions on compensation factors, based on these findings PT Oranje Nutrisi Global Semarang should evaluate the compensation given to its employees because to pay more attention to compensation adjustments to the performance that employees have given because compensation has the most influence